Association of class II human leukocyte antigen (HLA) alleles with pulmonary sarcoidosis - Esendagli, Dorina; Ozmen, Fusun; Koksal, Deniz; Onder, Sevgen; Emri, Salih (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background and objectives: Sarcoidosis is a systemic inflammatory disease of unknown etiology that involves any part of the body, mainly the lungs and thoracic lymph nodes. The clinical presentation is heterogeneous based on the degree and extent of organ involvement. The existence of variable clinical presentations and treatment responses suggest an important role of genetic predisposition. In genetic studies, sarcoidosis was found to be associated with several genes, but the strongest link was with HLA region. The aim of this study was to investigate the association of HLA class II alleles with the extent and course of disease in Turkish patients with sarcoidosis. Methods: The study included 103 patients with sarcoidosis and 100 unrelated healthy controls. HLA-DRB1 and HLA-DQB1 typing was performed by using Polymerase Chain Reaction-Sequence Specific Priming (PCR-SSP) method at low resolution level. Results: HLA-DRB1* and -DQB1* analysis revealed that while the frequency of HLA-DRB1*01 was significantly higher in the control group, HLA-DRB1*13 and -DQB1*06 alleles were more frequent in the sarcoidosis patients. When the patients were grouped based on clinical outcome as remitters and non-remitters, HLA-DRB1*10 allele was only detected in the remitters, whereas the frequency of HLA-DQB1*06 allele was significantly higher in non-remitters. Conclusions: This study supported the association of HLA alleles with sarcoidosis. In a considerably high number of patients with Turkish origin, the frequency of HLA-DRB1*13, -DRB1*10 and HLA-DQB1*06 alleles was significantly associated with increased risk and clinical outcome.